V Americe za války „před válkou“. Působení plk. gšt. Oldřicha Španiela v USA v letech 1939–1941 - Tomáš Jiránek (Theatrum Historiae)
During the Second World War, the Czechoslovak exile authorities were building military units which should have supported the efforts of the anti-fascist coalition. Shortly after the beginning of the war, colonel of the General Staff Oldřich Španiel was sent out to the USA to recruit among the local compatriot colonies and obtain the ranks for these units. The study deals with the ways of his work, co-operation with the local authorities, the relations among compatriots and the reasons why the results of the recruitment were relatively weak.